2010
DOI: 10.1111/j.1751-553x.2009.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent STAT3 activation is associated with Mcl‐1 expression in nasal NK‐cell lymphoma

Abstract: Nasal natural killer (NK)-cell lymphoma was resistant to various antitumor agents. Although high expression of p-glycoprotein has been reported, other molecular mechanism of the chemo-resistance is largely unknown. Activation of STAT3 and expression of major apoptosis-related proteins Bcl-2, Bcl-x, and Mcl-1 were analyzed by immunohistochemistry. Effects of STAT3 inhibitor AG490 on NK-YS cell line were analyzed by Western blotting and flow cytometric apoptosis assay. STAT3 was activated in six of the nine nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…Mcl-1 is a Bcl-2 family member that negatively regulates both apoptosis and autophagy [31,32]. This molecule has been previously reported to be reduced by AG490 treatment [33,34] and more recent studies have reported that also HSF1 can influence Mcl-1 expression [35]. However, a link between AG490, HSF1 and Mcl-1 molecules was not previously reported.…”
Section: Discussionmentioning
confidence: 93%
“…Mcl-1 is a Bcl-2 family member that negatively regulates both apoptosis and autophagy [31,32]. This molecule has been previously reported to be reduced by AG490 treatment [33,34] and more recent studies have reported that also HSF1 can influence Mcl-1 expression [35]. However, a link between AG490, HSF1 and Mcl-1 molecules was not previously reported.…”
Section: Discussionmentioning
confidence: 93%
“…The effect of resveratrol on the activation state of STAT-3 was investigated in EBV-infected B cells, since STAT-3 signal activation is implicated in the EBV-mediated oncogenesis [24], and previous studies have shown that resveratrol is an effective STAT-3 inhibitor [25], [26]. Whole-cell protein extracts were collected from EBV-infected B cells at 72 hrs after infection and assayed by Western blotting, with antibodies specific to phosphorylated STAT-3 at Tyr 705.…”
Section: Resultsmentioning
confidence: 99%
“…Although we were able to validate the importance of Elk-1 in controlling Mcl-1 expression we found that knockdown of SRF had little or no effect on basal or induced Mcl-1 expression (Supplementary Figure 2) Whether this is due to insufficient knockdown, recruitment of other co-activators in the absence of SRF or Elk-1 acting independently is yet to be determined. Although many additional transcription factor binding sites were found within the Mcl-1 promoter such as Stat-3 and NF-κB, two transcription factors that may have a role in Mcl-1 regulation in other cell types, it appears that these sites are not critical for the EGF induced regulation of Mcl-1 in these breast cancer cell lines (Boucher et al , 2000; Henson et al , 2006; Liu et al , 2003; Tsutsui et al , 2009). Furthermore, knockdown of both Stat-3 and NF-κB had no observable effect on basal or EGF induced Mcl-1 protein levels (Supplementary Figure 2A).…”
Section: Discussionmentioning
confidence: 97%